Peran Kiai Kampung Dalam Menanggulangi Radikalisme Keagamaan Di Sumenep Madura - Arif, Masykur (Tasamuh: Jurnal Studi Islam, 2023)
The post-reform religious radicalism movement has so far disturbed the community, including local religious leaders, such as the village kiai. This research raises the views of the village kiai regarding religious radicalism and why religious radicalism needs to be addressed by the village kiai, as well as the strategies used by the village kiai in tackling religious radicalism. In particular, the purpose of this research is to find out the role of village kiai in tackling religious radicalism. The subject of this research is village kiai who live in Sumenep, Madura. This research resulted in findings; first, the village kiai understands that religious radicalism is a manifestation of a violent or violent attitude. Religious radicalism is also a religious movement and concept that deviates from the norm. Second, the village kiai's factors in tackling radicalism are because they are not in accordance with the pesantren tradition, unsettle the community, understand religion superficially, and want to radically change religious traditions. Third, the efforts made by the village kiai to deal with religious radicalism are through three things, namely prevention, resistance, and prayer.